Multiplex HRM analysis as a tool for rapid molecular authentication of nine herbal teas. (February 2016) - Xanthopoulou, Aliki; Ganopoulos, Ioannis; Kalivas, Apostolos; Osathanunkul, Maslin; Chatzopoulou, Paschalina; Tsaftaris, Athanasios; Madesis, Panagiotis
Abstract: Herbal infusions, commonly referred to as herbal teas are among the most widely consumed hot beverages. Herbal tea authenticity is an issue of food safety. Reliable test methods, which could identify the botanical origin of herbal tea products, are required in order to protect the consumer from fraud and authenticate genuine products considering also the potential medical use of the herbs. Herein, we present a method that enables the simultaneous and reliable identification of 9 herbal species of sage, Greek sage, chamomile, mountain-tea, oregano, Cretan oregano, yarrow, lemon balm and rosemary. A high resolution melting (HRM) assay, targeting a fragment of the internal transcribed spacer 2 (ITS2) gene, was developed in order to authenticate the botanical origin of the herbal teas and their mixtures. Species-specific primers were designed and combined in a multiplex PCR resulting in fragments of different length and therefore different melting behavior for each species. The method was developed using dried tissue from each of the nine species. The multiplex HRM assay proposed in this work can be applied as routine tests for the verification of botanical origin in herbal teas and can be extended to authenticate all types of herbal foodstuffs. Highlights: We developed HRM assay targeting a fragment of the ITS2 gene. Simultaneous and reliable identification of 9 herbal species. Multiplex HRM analysis for rapid authentication of herbals.